Mirrors Of Entrepreneurial Foresight: A Qualitative Study As Seen Through The Lens Of Female Entrepreneurs In ICT - Vien, Truc-Mai Jenny (My University, 2024)
Navigating in an uncertain and volatile sector requires the implementation of foresight to identify business opportunities and to attain a competitive advantage. This thesis aims to explore images of the future of female entrepreneurs in ICT through the lens of business opportunities and digital skills to determine their outlook on the digitalisation. To further assess the application of foresight in an organisation, this thesis focuses on the approaches that female entrepreneurs utilise to conduct foresight practices in their everyday processes. The research approach adopted in this thesis includes qualitative methods that were executed through eight interviews with female entrepreneurs from ICT with less than 20 employees and who are based in Finland. A qualitative content analysis was employed to uncover emerging themes. The results indicate that three future images could be distinguished: Community Before All, Green World and Seeing The World Through Smart Glasses. These images reveal business opportunities related to the gaming industry and emerging technologies (e.g. AI). The most striking result to surface from the data is the alignment between a business opportunity and the values of female entrepreneurs as a critical factor. The findings also underline that female entrepreneurs implement foresight practices, ranging from thought experiments to horizon scanning. However, collaborative foresight practices within inter-firm structures were not adopted. It was evident that the present orientation of female entrepreneurs, accompanied by their misconceptions about foresight, tight financial budgets and time constraints influence how the future is perceived. The main conclusion to be drawn from this work is that female entrepreneurs’ images of the future concern building a community to induce social change and achieving environmental sustainability, therefore demonstrating the aspiration to tackle global challenges. Contrary, the counterimage focuses on technological advancements and generating profit. The present orientation of female entrepreneurs and the gap between the research of futures studies and the practitioners present core challenges when considering the practical implications to promote the application of foresight.
Keywords: Images of the future, entrepreneurial foresight, foresight practices, female entrepreneurs, ICT